Legal Review of Misuse of Personal Portraits in WhatsApp Stickers - Sandi S, Renda; Surya P, Dhika (Communication in Research and Publications (CRP), 2024)
The development of information technology has facilitated digital communication, but has also opened up opportunities for privacy abuse, especially in the use of personal portraits without permission as WhatsApp stickers. This study analyzes the legal aspects, socio-psychological impacts, and prevention efforts related to the illegal use of personal portraits on digital platforms. Through a comprehensive review of Indonesian laws and regulations, the study reveals the complexity of personal data protection in the digital era. The results of the study show that despite the existence of a regulatory legal framework, there are still significant challenges in law enforcement, public awareness, and prevention technology. This study emphasizes the need for a multidimensional approach involving public education, strengthening regulations, and collaboration between the government, digital platforms, and law enforcement agencies to protect individual privacy rights.